The Impact of Microbiota on Musculoskeletal Injuries - Giada La Placa; Marcello Covino; Marcello Candelli; Antonio Gasbarrini; Francesco Franceschi; Giuseppe Merra (Cells)
Musculoskeletal injuries comprise a wide range of physical conditions impacting the coordination of bones, muscles, and joints. Estimations suggest that close to one-third of the world’s population will experience a musculoskeletal or non-musculoskeletal injury at some point in their life. Musculoskeletal injuries affect athletes, office workers, industrial workers, older adults, and children every year. Among individuals over the age of 65, musculoskeletal injuries disproportionately affect older women, limiting their ability to maintain an active and professional life or engage in leisure activities during retirement. The field of physical therapy has recently expanded to build an understanding of the complex, non-linear interactions between the gut microbiota and the musculoskeletal system. There is an unexpected connection between the gut microbiota and both the experience of musculoskeletal pain and the healing process following musculoskeletal injuries. Understanding the mechanisms of the microbiota’s influence on these injuries could inform healthcare strategies aimed at prevention and recovery. For patients who suffer from or are at risk of developing musculoskeletal injuries, analyzing the composition of their microbiota plays a crucial role in patient stratification, which can significantly enhance the effectiveness of prevention and treatment strategies.